(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article examines the prospects for the development of the digital government system in Uzbekistan by 2030. The authors analyze the main directions of development of digitalization of public administration, highlight key problems and challenges, and also propose ways and mechanisms for solving them.